Red light delays programmed cell death in non-host interaction between Pseudomonas syringae pv tomato DC3000 and tobacco plants - Moyano, Laura (2020)
Light modulates almost every aspect of plant physiology, including plant-pathogen interactions. Among these, the hypersensitive response (HR) of plants to pathogens is characterized by a rapid and localized programmed cell death (PCD), which is critical to restrict the spread of pathogens from the infection site. The aim of this work was to study the role of light in the interaction between Pseudomonas syringae pv. tomato DC3000 (Pto DC3000) and non-host tobacco plants. To this end, we examined the HR under different light treatments (white and red light) by using a range of well-established markers of PCD. The alterations found at the cellular level included: i) loss of membrane integrity and nuclei, ii) RuBisCo and DNA degradation, and iii) changes in nuclease profiles and accumulation of cysteine proteinases. Our results suggest that red light plays a role during the HR of tobacco plants to Pto DC3000 infection, delaying the PCD process.